The Correlation Of Waist Circumference And Waist Hip Circumference Ratio With Vital Lung Capacity in Collage Students - Nurul Aini Rahmawati; Siti Ainun Ma'rufa; Shinta Kurnia Febriliani (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Final college students tend to lack physical activity accompanied by unhealthy lifestyles, this habit can disrupt body metabolism and potentially cause obesity. Obesity is a risk factor for various conditions including cardiorespiratory disorders. This is related to the accumulation of fat in the abdomen affecting the limitation of respiratory muscle performance. This study aims to determine the correlation between waist circumference and waist-hip ratio (WHR) with lung vital capacity in students. This observational study used a cross-sectional study with the proportionate stratified random sampling method on final-year students of Physiotherapy S1, University of Muhammadiyah Malang. Data collection was done using anthropometric measurements of waist circumference and waist-hip ratio using Medline and lung vital capacity using a spirometer. Data analysis used univariate and bivariate with the Spearmen's Rho test. The study's results obtained 127 students, consisting of 37 men and 90 women. Waist circumference of 58,3% of normal subjects, waist-hip ratio of 77,2% normal, and lung vital capacity value of 79,8% of normal subjects. The results of the hypothesis test of this study showed no significant relationship between waist circumference and waist-hip ratio with lung vital capacity with a value of p> 0,05 (p = 0,091 and p = 0,341). The correlation test of waist circumference was negatively correlated but not significant (r = -0,151 & r = 0,085). As the negative correlation value states, the higher the waist circumference, the lower the lung vital capacity. In contrast, the waist-hip ratio did not correlate significantly with lung vital capacity. This study concludes that there is no relationship between waist circumference and waist-hip ratio with lung vital capacity.